Proteome driven re-evaluation and functional annotation of the Streptococcus pyogenes SF370 genome - Okamoto, Akira (BioMed Central, 2011)
BACKGROUND: The genome data of Streptococcus pyogenes SF370 has been widely used by many researchers and provides a vast array of interesting findings. Nevertheless, approximately 40% of genes remain classified as hypothetical proteins, and several coding sequences (CDSs) have been unrecognized. In this study, we attempted a shotgun proteomic analysis with a six-frame database that was independent of genome annotation. RESULTS: Nine proteins encoded by novel ORFs were found by shotgun proteomic analysis, and their specific mRNAs were verified by reverse transcriptional PCR (RT-PCR). We also provided functional annotations for hypothetical genes using proteomic analysis from three different culture conditions that were separated into three fractions: supernatant, soluble, and insoluble. Consequently, we identified 567 proteins on re-evaluation of the proteomic data using an in-house database comprising 1,697 annotated and nine non-annotated CDSs. We provided functional annotations for 126 hypothetical proteins (18.9% out of the 668 hypothetical proteins) based on their cellular fractions and expression profiles under different culture conditions. CONCLUSIONS: The list of amino acid sequences that were annotated by genome analysis contains outdated information and unrecognized protein-coding sequences. We suggest that the six-frame database derived from actual DNA sequences be used for reliable proteomic analysis. In addition, the experimental evidence from functional proteomic analysis is useful for the re-evaluation of previously sequenced genomes.